PENGARUH KOMPENSASI DAN MOTIVASI SERTA DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KSP SATYA DHARMA DI DENPASAR - AGUS PUTRA MARDIKA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to (1) determine the effect of compensation on employee performance, (2) determine the effect of compensation on employee performance discipline, (3) determine the effect of motivation on employee work discipline, (4) determine the effect of motivation on employee performance, (5) the effect of motivation on employee performance. work discipline on employee performance, (6) knowing how work discipline mediates the effect of compensation on employee performance, (7) knowing how work discipline mediates the effect of motivation on employee performance. This research was conducted at KSP Satya Dharma in Denpasar. Employee performance is important for the company to achieve its goals. Creating good employee performance is not easy because employee performance can be created if there are things that affect it and can be properly accommodated and accepted by employees within a company. In this study, employee performance is influenced by compensation, work discipline and work motivation. The respondents of this study were 65 employees of KSP Satya Dharma in Denpasar. The results of this study indicate that: (1) Compensation has a negative and insignificant effect on work discipline not proven, (2) Compensation has a negative and insignificant effect on employee performance not proven, (3) work motivation has a positive and significant influence on discipline proven work. (4) work motivation has a positive and insignificant effect on employee performance, (5) work discipline has a positive and significant influence on employee performance, (6) work discipline is not a mediating variable between work discipline on employee performance, (7) work discipline mediate the relationship between work motivation and employee performance.